Maintaining Moisture in Dehydrated Skin with Hyaluronic Acid - Silkinaitė, Smiltė; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2024)
Moisturising the skin is an important aspect of maintaining healthy skin and its protective function. Moisturising cosmetic products, often used both in daily skincare and in the treatment of skin diseases, have the function of improving the skin’s moisture level, especially when the skin becomes dry and is damaged by exogenous and endogenous factors [1]. The stratum corneum barrier in the epidermis of the skin is responsible for water retention in the skin. If the stratum corneum is damaged, the skin’s moisture is lost and the skin becomes dehydrated [2]. Objective. To analyze the maintenance of moisture in dehydrated skin utilizing hyaluronic acid. Methods. A review of scientific articles using the keywords: dehydrated skin, skin problems, moisture retention, lipid function, hyaluronic acid, and combinations of hyaluronic acid with the words ‘and’, ‘or’ has been performed. The articles were searched in PubMed, Google Scholar, BMJ, Clinics Dermatology, International Journal of biological macromolecules electronic databases. The literature review included 25 freely available and full-length articles on the topic, written in English, between 2014 and 2023. Results. This article discusses the causes of dehydrated skin, the effect of external and internal factors on the skin, the profound effect of cosmetic products containing hyaluronic active ingredients on dehydrated skin, preservation of skin moisture, and the importance of preventive measures. Conclusions. 1. Skin dehydration is caused by the body’s exposure to external and internal factors, low lipid levels, damage to the skin’s protective barrier and the stratum corneum, and the presence of dry and sensitive skin types. 2. The water transport function of the hydrophilic molecules of hyaluronic acid is important for the maintenance of the skin’s hydrodynamics, and this process maintains the skin’s moisture level and tissue elasticity and prevents the evaporation of water from the skin’s surface and dehydration.